Det værendes væren og det sociales socius : Et bidrag til studiet af ’Heidegger-Latour-forbindelsen’ - Schiølin, Kasper (STS Encounters, 2013)
In recent times different scholars have tried to combine the philosophies of Martin Heidegger and Bruno Latour. Hoping to investigate and develop this philosophical borderland further and thereby take part in opening up a theoretical resource for philosophers as well as sociologists, this paper adds another perspective to the ‘Heidegger-Latour-connection’. The paper takes a linguistic perspepective as it deals with the more or less explicit grammatical dimensions in Heidegger and Latour’s thinking. It is argued that both are pushing and squeezing their core notions in the direction of the verbs, rather than, as usually done in sociology and philosophy, the nouns. Both are doing so in order to avoid essentialism, where truth is expressed in nouns (substantives), which they both accuse the tradition to succumb to. This indicates a similarity in their thinking, which especially stems from their philosophies’ inclusion of things and technologies.